(untitled) (Reflection and Critique Law Magazine, 2020)
This article possible the discussion about the industrial production and the practice of the obsolescence programmed under the environmental prism, covering the increasing production and disposal of solid waste, advocating for the formulation of legislation before the existing legal gap regarding the regulation and typification of the planned obsolescence in relation to the National Solid Waste Policy. In this sense, with the growth of production and disposal of solid waste in the country, it is necessary to guarantee and ensure the establishment of guidelines that favor the consumer markets in the acquisition of products of greater durability, products with viability and technological compatibilities that enable a longer life cycle.